Optimization of synthetic conditions CMC-g-poly (acrylic acid)/Celite composite superabsorbent by Taguchi method and determination of its absorbency under load (eXPRESS Polymer Letters)
A novel biopolymer-based composite hydrogel was synthesized through chemical crosslinking by graft copolymerization of partially neutralized acrylic acid onto the carboxymethyl cellulose (CMC). The Taguchi method, a robust experimental design, was employed for the optimization of the synthesis based on the swelling capacity of the hydrogels. This method was applied for the experiments and standard L16 orthogonal array with five factors and four levels. In the synthesis of the composite superabsorbent, N,N'-methylene bisacrylamide (MBA) as crosslinker, ammonium persulfate (APS) as initiator, acrylic acid (AA) as monomer, CMC/Celite weight ratio and neutralization percent (NU) were used as important factors. From the analysis of variance of the test results, the most effective factor controlling equilibrium swelling capacity was obtained and maximum water absorbency of the optimized final product was found to be 310 g/g. The surface morphology of the gel was examined using scanning electron microscopy. Furthermore in this research, swelling capacity of composite SAPs was determined under realistic condition (saline solution absorbency under load).